Relación entre clima laboral y satisfacción laboral en organizaciones públicas y privadas - Castro Vega, Sandra (2021)
The work environment is a psychological variable that is directly related to job satisfaction within the organizational context. The aim of this study is to relate work environment and job satisfaction in public and private organizations. To this end, a systematic review of the literature was conducted, taking in consideration only those that followed PRISMA guidelines (Urrutia & Bonfill, 2010). The following databases were used with the predefined inclusion criteria (Work environment and job satisfaction) Proquest, Psicodoc, Redalyc and Scielo. Studies that related work environment with job satisfaction in an organizational context were selected for analysis. After applying the inclusion and exclusion criteria, the search was reduced to seven quantitative crosssectional studies for evaluation and analysis. As a result, a positive correlation was observed between work environment and job satisfaction (Noboa et al., 2019; Pedraza, 2020; Pupo-Guisado et al., 2017). A pleasant work environment will correspond to greater job satisfaction. In general, the quality of the studies was considered average. Future studies should take in consideration the use of longitudinal, experimental studies, with pre and post tests to identify which factors have the greatest influence on the variables analyzed